ChemInform Abstract: Rhodium‐Catalyzed Oxidative C—H Activation/Cyclization for the Synthesis of Phosphaisocoumarins and Phosphorous 2‐Pyrones. Issue 19 (13th May 2014) - Park, Youngchul; Seo, Jungmin; Park, Sangjune; Yoo, Eun Jeong; Lee, Phil Ho
Abstract Rhodium‐catalyzed cyclizations of phosphinic acids and phosphonic monoesters with alkynes are developed.